2023
DOI: 10.7759/cureus.35416
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes Between Culture-Positive and Culture-Negative Sepsis and Septic Shock Patients: A Meta-Analysis

Abstract: This meta-analysis has been conducted to compare the clinical outcomes between culture-positive and culture-negative sepsis or septic patients. The present meta-analysis is reported as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Electronic databases, including PubMed and EMBASE, were searched by two authors independently from the inception to January 25, 2023, using the following key terms: "culture positive," "culture negative," "sepsis," and "septic shock."… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…They did not characterize the culture-negative patients regarding chronic use of medications (23). In their metanalysis of 10 studies, involving almost 24,000 patients, Afzai et al compared the clinical outcomes of culturepositive vs. culture-negative patients and found that there were no signi cant differences in all-cause mortality, need for mechanical ventilation, hemodialysis and length of ICU stay (24). They did not address potential etiologies for hypotension amongst their culture-negative patients as well, and therefore, it could be argued that other causes for deterioration enhanced the death of patients whose cultures turned to be negative.…”
Section: Discussionmentioning
confidence: 99%
“…They did not characterize the culture-negative patients regarding chronic use of medications (23). In their metanalysis of 10 studies, involving almost 24,000 patients, Afzai et al compared the clinical outcomes of culturepositive vs. culture-negative patients and found that there were no signi cant differences in all-cause mortality, need for mechanical ventilation, hemodialysis and length of ICU stay (24). They did not address potential etiologies for hypotension amongst their culture-negative patients as well, and therefore, it could be argued that other causes for deterioration enhanced the death of patients whose cultures turned to be negative.…”
Section: Discussionmentioning
confidence: 99%